(untitled) (International Journal of Engineering and Computer Science, 2017)
The advantage of Mobile Ad-hoc Networks (MANETs) is to form a wireless network in the absence of fixed infrastructure. . In defining and managing trust in a military MANET, we must consider the interactions between the composite cognitive, social, information and communication networks, and take into account the severe resource constraints. We provide a survey of trust management schemes developed for MANETs and discuss generally accepted classifications, potential attacks, performance metrics, and trust metrics in MANETs. Finally, we discuss future research areas on trust management in MANETs based on the concept of social. AODV node is able to discover multiple loop-free paths as candidates in one route discovery. These are evaluated by two values hop count and trust values. In this paper we discuss about trust value and improves the packet ratio